Creativity for service innovation: a practice‐based perspective. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – The success of service innovation is largely dependent on creativity. So far, however, the question of how to reinforce creativity in the development of innovative services, while being an important managerial issue, has not attracted much attention from the academics. The purpose of this paper is to fill in this gap, by studying what constitutes capabilities for reinforcing creativity in service innovation, from a practice‐based perspective.Design/methodology/approach – Through the theoretical lens of the resource‐based view we set out to conduct three case studies in highly service‐innovative European research and technology organisations (RTOs). Through 24 interviews and analysis of secondary sources, we collect our data, which are then analysed from a multi‐case perspective, in order to gain understanding on the resource‐related practices and resulting capabilities for reinforcing creativity in service innovation.Findings – By studying the resource‐related practices of reinforcing creativity in service innovation, this study brings about seven relevant capabilities; namely attracting, stimulating, combining, providing, breeding, opening up and accepting. In this perspective, our work represents an important theoretical contribution in terms of explicitly proposing specific capabilities for reinforcing service innovation creativity.Originality/value – The research is original for a couple of reasons. First, creativity in service innovation has not been explicitly studied before, especially through empirical research. Second, our findings offer a set of original capabilities propositions that can be practically applied in service‐innovative organisations. Finally, our research is carried out in a novel field, as RTOs have rarely been studied regarding service innovation‐related creativity, even though they represent a very interesting type of organisations in this perspective. Acknowledgements : Research carried out in this contribution has been funded by the National Research Fund, Luxembourg.